Characterization of structural, electrical conductivity and dielectric properties of 1',3'-dihydro-1',3',3'-trimethyl-6-nitrospiro[2H-1benzopyran-2,2'[2H] indole] compound - E.E. Elgarhy; M.M. El-Nahass; H.A. Zayed; H. A. M. Ali (Journal of Scientific Research in Science, 2021)
The structural properties of 1',3'-dihydro-1',3',3'-trimethyl-6-nitrospiro [2H-1-benzopyran-2,2'-[2H]indole] (DTNBI) characterized using X-ray diffraction. DTNBI's powder has a monoclinic polycrystalline structure. The DTNBI's lattice constant of unit cell are ( a = 29.912 Å, b = 18.815 Å, and c = 13.062 Å). The mean crystallite size and strain were evaluated using the formula of Scherrer, Williamson-Hall, and Size-Strain plots methods. In the frequency range of 40 to 5×106 Hz, the dependence of ac conductivity was studiedforthe bulk DTNBI upon different temperatures (303-363 K). The prevailing mechanism for the ac conduction was the correlated barrier hopping model for bulk DTNBI.The dielectric constant and the dielectric loss were also studied. The dielectric polarization mechanism of bulk DTNBI used to explain the behavior of the real, ε1, and imaginary, ε2, components of the complex dielectric constant. Reliance of dc and ac conductivity of bulk DTNBI follows the law of Arrhenius. The activation energy of both dc and ac conduction for bulk DTNBI were calculated and the dielectric characteristics were examined via complex electric modulus formalism.